The mediating effect of work motivation on the relationship between transformational leadership and employee performance - Bimmo Dwi Baskoro; Fuadi Fuadi; Heri Sapari Kahpi (Jurnal Kajian Manajemen dan Wirausaha, 2021)
This research aimed to analyze the influence of transformational leadership (TL) on employee performance (EP) through work motivation (WM) on engineering consulting companies in Capital Region of Jakarta. The data collection of this research was primary and secondary by using structural equation modeling with partial least squares method. The total respondent of this research was 106 who were the employees from selected engineering consulting companies in Capital Region of Jakarta. TL had a significant effect towards EP. TL had a significant effect towards WM. Lastly, TL had a significant effect towards EP through work motivation.